DINIY BARQAROR BIRIKMALARNING STILISTIK XUSUSIYATLARI - Xudoynazarova, O‘g‘lonoy (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In this article, the stylistic characteristics of stable religious compounds, their acquisition of different meanings in different situations, and their appearance in the form of anaphora, epithet, phrase, alliteration, antithesis in them are revealed with the help of vivid examples.